RESPON MAHASISWA PENDIDIKAN BAHASA JEPANG ANGKATAN 2020 TERHADAP MEDIA AUDIO VISUAL TATA BAHASA JEPANG UKEMI - Fadli Astira; Merri Silvia Basri; Adisthi Martha Yohani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study describes how the response of Japanese language education students batch 2020 to the audio-visual media of Japanese grammar ukemi. The purpose of this study was to determine the response of Japanese language education students batch 2020 to Ukemi's Japanese grammar audio-visual media. This study uses the analytical method popularized by Sudjana (2011). The results of this study are that the researchers received responses from students, as many as 19 people rated it very decent, 2 people rated it worthy, 4 people rated it less worthy, and 2 people rated it not worth it. Various responses, namely the learning videos are interesting, can help in more detailed grammar, and so onKey Words: Ukemi, Student Response, Audio-visual media